Constructing heterojunctions by surface sulfidation for efficient inverted perovskite solar cells - Li, Xiaodong; Zhang, Wenxiao; Guo, Xuemin; Lu, Chunyan; Wei, Jiyao; Fang, Junfeng (Science (American Association for the Advancement of Science), 2022)
A stable perovskite heterojunction was constructed for inverted solar cells through surface sulfidation of lead (Pb)–rich perovskite films. The formed lead-sulfur (Pb-S) bonds upshifted the Fermi level at the perovskite interface and induced an extra back-surface field for electron extraction. The resulting inverted devices exhibited a power conversion efficiency (PCE) >24% with a high open-circuit voltage of 1.19 volts, corresponding to a low voltage loss of 0.36 volts. The strong Pb-S bonds could stabilize perovskite heterojunctions and strengthen underlying perovskite structures that have a similar crystal lattice. Devices with surface sulfidation retained more than 90% of the initial PCE after aging at 85°C for 2200 hours or operating at the maximum power point under continuous illumination for 1000 hours at 55° ± 5°C. Perovskite solar cells (PSCs) with high power conversion efficiency (PCE) and stability have been reported in regular n-i-p devices, but inverted p-i-n PSCs that could be easier to use in tandem solar cells usually have lower PCEs (22 to 23%) Li et al . sulfurized a lead-rich layer with hexamethyldisilathiane, and the lead-sulfur bonds shifted the Fermi level of perovskite-transporter layer interface to create an electric field that enhanced electron extraction. The inverted PSCs had PCEs >24%, and the strong lead-sulfur bonds helped to maintain >90% of this efficiency during illuminated operation for 1000 hours at 55°C and after dark aging at 85°C for 2200 hours. —PDS Surface sulfidation of perovskite film increases its stability and improves electron extraction through band bending.